Birth rate, perinatal mortality and infant mortality in Ukraine: evolution from 1991 to 2021 and current risks - O.P. Volosovets; А.E. Abaturov; G.V. Beketova; V.M. Zabolotko; N.G. Rudenko; S.P. Kryvopustov; А.O. Volosovets; I.O. Loginova; L.M. Korkh (Zaslavsky O.Yu., 2022)
Ukraine is one of the poorest countries in Europe and currently is under attack of Russian troops. In recent decades, birth rate in Ukraine has been steadily declining by 47 %, and infant and perinatal mortality rates remain among the highest positions in Europe. Infant mortality, perinatal mortality, early neonatal mortality, and stillbirth rates in Ukraine have more than halved in 30 years and are lower than in the CIS countries, but still exceed those in the European Union. There is a downward trend in characteristics of all components of perinatal mortality; more for intranatal mortality, less for early neonatal mortality, whose share in the structure has increased in recent years, which requires improving the quality of medical care for newborns and taking measures for antenatal protection of the fetus. The fact that early neonatal mortality rates in Ukraine may be underestimated due to shortcomings in the registration of live births and stillbirths is worrying. Congenital malformations and conditions that appeared during pregnancy and childbirth in women who give birth to children with very low and extremely low body weight dominate among the causes of perinatal mortality in Ukraine. An effective way to reduce child losses in Ukraine during the last decade was the introduction of modern perinatal technologies to prevent pathological conditions in mothers and babies with extremely low and very low body weight, the continuation of the creation and restoration of a network of perinatal centers and proper conditions for safe childbirth in the regions of the country with the help of international aid, timely diagnosis and treatment of conditions that occur in the perinatal period and congenital malformations. An important resource for reducing infant and perinatal mortality in Ukraine and increasing the birth rate will be the stabilization of the sociopolitical situation in the country and appropriate international assistance in restoring the health care system, aimed at improving both somatic and reproductive health of future parents, especially mothers, forming in them a conscious and proper attitude to parenthood and care for the newborn.